Comparison of Utilization an Absorption and Vapour Compression Chiller in Sub-Tropical Country Building – A Feasibility Study - Simbolon, Luga Martin; Hikmat, Yudi Prana (Bandung State Polytechnic (Politeknik Negeri Bandung), 2020)
The present study investigate the feasibility of absorption chiller utilization as part of trigeneration system that possibly applied in sub-tropical country building. Trigeneration is refer to the heat utilisation from electric generator (combined heat and power, CHP) to generate absorption chiller in order to produce chilled water for air conditioning system (combined cooling, heat and power, CCHP). Compare to the vapour compression system, absorption chiller that is mainly generated by heat waste, promised benefit economically and environmentally. Overall efficiency of CCHP can reach 71 % and possibly reducing emission until 146709.07 kg CO2. Economic analysis using the Payback period methodology has shown that the CCHP would produce a return on investment of 2.6 years. Improvements absorption chiller and support from government are expected to lead to increased return on investment and improved viability of the system.